Neonatal high protein intake enhances neonatal growth without significant adverse renal effects in spontaneous IUGR piglets. Issue 10 (29th May 2017) - Boubred, Farid; Jamin, Agnes; Buffat, Christophe; Daniel, Laurent; Borel, Patrick; Boudry, Gaëlle; Le Huëron‐Luron, Isabelle; Simeoni, Umberto
Abstract: In humans, early high protein (HP) intake has been recommended to prevent postnatal growth restriction and complications of intrauterine growth restriction (IUGR). However, the impact of such a strategy on the kidneys remains unknown, while significant renal hypertrophy, proteinuria, and glomerular sclerosis have been demonstrated in few experimental studies. The objective of this study was to evaluate the effects of a neonatal HP formula on renal structure in IUGR piglets. Spontaneous IUGR piglets were randomly allocated to normal protein (NP, n = 10) formula or to HP formula (+50% protein content, n = 10) up to day 28 after birth. Body weight, body composition, renal functions, and structure were assessed at the end of the neonatal period. While birth weights were similar, 28‐day‐old HP piglets were 18% heavier than NP piglets ( P < 0.01). Carcass protein content was 22% higher in HP than in NP offspring ( P < 0.01). Despite a HP intake, kidney weight and glomerular fibrosis were unaltered in HP piglets. Only a 20% increase in glomerular volume was noted in HP piglets ( P < 0.05) and restricted to the inner cortical area nephrons ( P = 0.03). Plasma urea/creatinine ratio and proteinuria were unchanged in HP piglets. In conclusion, neonatal HP feeding in IUGR piglets significantly enhanced neonatal growth and tissue protein deposition but mildly affected glomerular volume. It can be speculated that a sustained tissue protein anabolism in response to HP intake have limited single nephron glomerular hyperfiltration. Abstract : In humans, early high protein (HP) intake has been recommended to prevent postnatal growth restriction and complications of intrauterine growth restriction (IUGR). However, the impact of such a strategy on the kidneys remains unknown. In this study, we showed that feeding spontaneous born IUGR piglets with a HP formula significantly enhanced neonatal growth and tissue protein deposition but only induced a moderate glomerular hypertrophy. It can be speculated that glomerluar hyperfiltration and hypertrophy were limited by enhanced tissue protein deposition in response to HP intake.